Atomic Oxygen Retrieved From the SABER 2.0‐ and 1.6‐μm Radiances Using New First‐Principles Nighttime OH(v) Model. Issue 11 (14th June 2018) - Panka, Peter A.; Kutepov, Alexander A.; Rezac, Ladislav; Kalogerakis, Konstantinos S.; Feofilov, Artem G.; Marsh, Daniel; Janches, Diego; Yiğit, Erdal
Abstract: The recently discovered fast, multiquantum OH( v )+O( 3 P) vibrational‐to‐electronic relaxation mechanism provided new insight into the OH( v ) Meinel band nighttime emission formation. Using a new detailed OH( v ) model and novel retrieval algorithm, we obtained O( 3 P) densities in the nighttime mesosphere and lower thermosphere (MLT) from the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) 2.0‐ and 1.6‐μm radiances. We demonstrate how critical the new OH( v ) relaxation mechanism is in the estimation of the abundance of O( 3 P) in the nighttime MLT. Furthermore, the inclusion of this mechanism enables us to reconcile historically large discrepancies with O( 3 P) results in the MLT obtained with different physical models and retrieval techniques from WIND Imaging Interferometer, Optical Spectrograph and Infrared Imager System, and Scanning Imaging Absorption Spectrometer for Atmospheric Chartography observations of other airglow emissions. Whereas previous SABER O( 3 P) densities were up to 60% higher compared to other measurements the new retrievals agree with them within the range (±25 % ) of retrieval uncertainties. We also elaborate on the implications of this outcome for the aeronomy and energy budget of the MLT region. Plain Language Summary: The recently discovered fast hydroxyl‐atomic oxygen relaxation mechanism provided new insight into the mesospheric emission formation. Using a new hydroxyl (OH) model and retrieval algorithm, we obtained atomic oxygen concentration in the nighttime mesosphere and lower thermosphere (MLT) from the SABER OH radiances. We demonstrate how critical this new relaxation mechanism is in the estimation of the abundance of atomic oxygen in the nighttime MLT. Furthermore, the inclusion of this mechanism enables us to reconcile historically large discrepancies with atomic oxygen results in the MLT obtained with different physical models and retrieval techniques from WINDII, OSIRIS, and SCIAMACHY observations of other airglow emissions. Whereas previous SABER atomic oxygen densities were up to 60% higher compared to other measurements, the new retrievals agree with them within the range (±25 % ) of retrieval uncertainties. We also elaborate on the implications of this outcome for the aeronomy and energy budget of the MLT region. Key Points: New detailed non‐LTE OH( v ) model is applied to analyze SABER nighttime Meinel band emissions Novel two‐channel O( 3 P) retrieval technique uses SABER nighttime 2.0‐ and 1.6‐micrometer radiances New retrievals reconcile large differences with O( 3 P) derived from other airglows